Superficial and deep cutaneous fungal infections in solid organ transplant recipients - Berenika Olszewska; Beata Imko-Walczuk; Roman Nowicki; Alicja Dębska-Ślizień; Aleksandra Wilkowska; Bolesław Rutkowski (Termedia Publishing House, 2016)
Due to the fact that the number of solid organ transplant recipients is increasing, the population of immunosuppressed individuals is growing. Immunosuppression predisposes organ transplant recipients to the development of fungal infections that cause not only graft failure but also mortality. Immunosuppression makes diagnosis difficult due to atypical signs and symptoms of mycoses. Treatment of infections may be complicated because of fungal resistance to commonly used drugs, drug interactions and the requirement to continue immunosuppression to avoid graft rejection. This article provides a review of superficial and invasive fungal infections within the skin, including diagnostic and therapeutic methods. Quick identification of the pathogen and appropriate treatment are essential to the life of patients.